Smectites and zeolites in ash from the 2010 summit eruption of Eyjafjallajökull volcano, Iceland - Paque, Mathilde; Detienne, Marie; Maters, Elena; Delmelle, Pierre (Bulletin of Volcanology, 2016)
Hydrothermal alteration minerals are often incorporated in volcanic ash from phreatic and phreatomagmatic activity. Here we assess the presence and abundance of such minerals in the ash materials produced during the April- May 2010 initial phreatomagmatic (phase I) and subsequent magmatic (phases II and III) eruptions of Eyjafjallajökull volcano, Iceland. The results of X-ray diffraction analyses reveal significant quantities of smectites (up to 4 wt%, mainly as saponite) and zeolites (up to 7 wt%) in ash from phase I. While a minor amount of smectites (<0.5 wt%) is present in ash from the subsequent weak explosive activity (phase II), both smectites and zeolites are absent in phase III ash. This material was generated following abrupt rejuvenation of explosive activity in the absence of magma-ice/water interaction. Smectites and zeolites in phase I ash result primarily from scouring of altered volcanic rocks in the subsurface, although some may derive also from water-rock interaction within the summit ice cauldrons through which fragmented magma was injected.We show that incorporation of smectites and zeolites in phase I ash can explain its anomalously high specific surface area. Further, the presence of these minerals in ash may enhance its ability to act as ice nuclei as well as favour particle aggregation processes in the volcanic plume/cloud. Finally, the Eyjafjallajökull eruption represents another case in which ash fallout acted as an exogenic source of 2:1-type clay minerals in volcanic soils.